Seasonal scenario planning for matching seed supply and demand: Workshop format - Steinke, Jonathan; Ortíz Crespo, Berta (2022)
This document describes a workshop procedure for seasonal seed scenario planning. It is guided by a powerpoint presentation and revolves around jointly using the MS Excel tool for scenario planning, and leveraging informed decision-making on seed supply.